If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x(x-2)=5(x+4)
We move all terms to the left:
3x(x-2)-(5(x+4))=0
We multiply parentheses
3x^2-6x-(5(x+4))=0
We calculate terms in parentheses: -(5(x+4)), so:We get rid of parentheses
5(x+4)
We multiply parentheses
5x+20
Back to the equation:
-(5x+20)
3x^2-6x-5x-20=0
We add all the numbers together, and all the variables
3x^2-11x-20=0
a = 3; b = -11; c = -20;
Δ = b2-4ac
Δ = -112-4·3·(-20)
Δ = 361
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{361}=19$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-11)-19}{2*3}=\frac{-8}{6} =-1+1/3 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-11)+19}{2*3}=\frac{30}{6} =5 $
| 10+2m+1.25=1 | | 3q+2=11q-8 | | 6p-5=4p-15 | | x(4+11)=3 | | 8d-4=12d-14 | | 4x^2-8x+77=0 | | 3x+77x=33x+15 | | 9x-15=8x+7 | | x=500-(x*0.05) | | 6y^2+7y-5=0 | | 2x+5x=-14x+x | | 4-2t+t^2=0 | | U^2-5u+3=0 | | 6w^2=19w-8 | | 10y^2-26y=12 | | x×2+12×3=162 | | 1/5a+9=9 | | 4(3x+1)=-3(5x-4) | | 6(2l+3)=78 | | 18x+3=5(3x+1)+3x-2 | | y/5+5=9 | | (5x-1)(x+3)=(x-5)(5x+1)=40 | | 4×7^(4x)=49×2^(2x) | | 7(9-z)÷6=-z | | -6(2x-4)+6=-12x+30 | | 7-x/2=5x-4 | | 2(x+4)÷3=4x-4 | | 12x+16=140 | | 3x^2-3x-23=0 | | x+180-x=180 | | 8x/2+3=x-6 | | (2x^2+5x)^2-10x^2-25x-14=0 |